Attitudes and beliefs about deceased organ donation in the Arabic-speaking community in Australia: a focus group study. Issue 1 (19th January 2016) - Ralph, Angelique F; Alyami, Ali; Allen, Richard D M; Howard, Kirsten; Craig, Jonathan C; Chadban, Steve J; Irving, Michelle; Tong, Allison
Abstract : Objectives: To describe the beliefs and attitudes to organ donation in the Arabic-speaking community. Design: Arabic-speaking participants were purposively recruited to participate in 6 focus groups. Transcripts were analysed thematically. Participants: 53 participants, aged 19–77 years, and originating from 8 countries, participated in 1 of 6 focus groups. Participants identified as Christian (73%), Islam (26%), Buddhist (2%) or did not identify with any religion (2%). Results: 6 themes (with subthemes) were identified; religious conviction; invisibility of organ donation; medical suspicion; owning the decision; and reciprocal benefit. Conclusions: Although organ donation is considered a generous life-saving 'gift', representative members of the Arabic-speaking community in Australia were unfamiliar with, unnerved by and sceptical about the donation process. Making positive decisions about organ donation would likely require resolving tensions between respecting family, community and religious values versus their individual autonomy. Providing targeted education about the process and benefits of organ donation within the Arabic community may clarify ambiguities surrounding cultural and religious-based views on organ donation, reduce taboos and suspicion towards donation, and in turn, lead to increased organ donation rates.